2021
DOI: 10.1159/000517400
|View full text |Cite
|
Sign up to set email alerts
|

Breathlessness and COVID-19: A Call for Research

Abstract: Breathlessness, also known as dyspnoea, is a debilitating and frequent symptom. Several reports have highlighted the lack of dyspnoea in a subgroup of patients suffering from COVID-19, sometimes referred to as “silent” or “happy hyp­oxaemia.” Reports have also mentioned the absence of a clear relationship between the clinical severity of the disease and levels of breathlessness reported by patients. The cerebral complications of COVID-19 have been largely demonstrated with a high prevalence of an acute encepha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 101 publications
1
14
0
Order By: Relevance
“…Dyspnea or respiratory distress occurs due to several clinical conditions, but it is also a reflection of reduced cardiovascular fitness 55 . In COVID-19, it is related to inflammation of the pulmonary alveoli, thrombosis, microclots, and neuroinvasion 56 . In fact, it was shown that although 86% of 1,099 patients with COVID-19 had chest tomography abnormalities and a low relationship between the partial pressure of oxygen and fraction of inspired oxygen (PaO 2 /FiO 2 ), dyspnea was reported in only 18.6% 57 The variation in the perception of dyspnea may be caused by the neuroinvasive potential of SARS-CoV-2 due to the involvement of the cardiorespiratory center 58 or higher centers 56 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dyspnea or respiratory distress occurs due to several clinical conditions, but it is also a reflection of reduced cardiovascular fitness 55 . In COVID-19, it is related to inflammation of the pulmonary alveoli, thrombosis, microclots, and neuroinvasion 56 . In fact, it was shown that although 86% of 1,099 patients with COVID-19 had chest tomography abnormalities and a low relationship between the partial pressure of oxygen and fraction of inspired oxygen (PaO 2 /FiO 2 ), dyspnea was reported in only 18.6% 57 The variation in the perception of dyspnea may be caused by the neuroinvasive potential of SARS-CoV-2 due to the involvement of the cardiorespiratory center 58 or higher centers 56 .…”
Section: Discussionmentioning
confidence: 99%
“…In COVID-19, it is related to inflammation of the pulmonary alveoli, thrombosis, microclots, and neuroinvasion 56 . In fact, it was shown that although 86% of 1,099 patients with COVID-19 had chest tomography abnormalities and a low relationship between the partial pressure of oxygen and fraction of inspired oxygen (PaO 2 /FiO 2 ), dyspnea was reported in only 18.6% 57 The variation in the perception of dyspnea may be caused by the neuroinvasive potential of SARS-CoV-2 due to the involvement of the cardiorespiratory center 58 or higher centers 56 . These data suggest that impaired lung function is not the only mechanism responsible for triggering dyspnea in patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…From our data, we could not find any parameters at IRCU admission that help us to recognize the likelihood of worsening. Moreover, remaining longer in the general ward before IRCU transfer could be wrongly categorized as less severe than reliable (concept of silent hypoxia) [ 17 , 18 , 19 ]. At IRCU admission, these subjects got worse than expected and quickly deteriorated.…”
Section: Discussionmentioning
confidence: 99%
“…28 Breathlessness was the major red flag sign reported in our study, some studies reported fever and headache, while breathlessness was the most frequent and distressing symptom in some other studies. 29,30 Red flag signs have a role in decision-making and serve as a precursor to upcoming dangerous or lifethreatening events, making early detection and management of these signs essential for home-bound patients. 31 The findings highlight the need for creating awareness among the public regarding the significance of identification of red flag signs to prevent delays in shifting the patients to hospitals and to implement a HI monitoring mechanism (technology based).…”
Section: Discussionmentioning
confidence: 99%